Analysis of the Benefits of X-Ray Waves in Ultrasound: Literature Review - Aminatun, Aminatun; Sumo, Maimon; Muslimah, Muslimah; Mutmainnah, Mutmainnah; Islami, Yasmin Sabrina Nur (PT. Riset Press International, 2024)
In the information age like now, waves are very influential on human life. Almost all living creatures on earth are inseparable from the use of waves. One of them is X-ray and ultrasound waves. The use of X-rays and ultrasonic (USG) waves in various fields, especially in the health sector, is an important aspect of technological development. As well as its application in the medical and industrial fields. Electromagnetic waves, especially X-rays, have become an irreplaceable diagnostic instrument in visualizing the internal structure of the human body. The various benefits of X-rays are explained, from diagnosing bone fractures to radiotherapy treatment for cancer. On the other hand, ultrasound is used for pregnancy checks, monitoring the condition of the fetus, and detecting tumors and other disorders. Although ultrasound does not use direct X-ray waves, the integration of X-ray processing technology can increase image resolution and provide more comprehensive information. In this article, we will discuss several benefits of waves, namely X-ray and ultrasound waves. X-rays use electromagnetic waves with a higher frequency that are ionizing. Meanwhile, ultrasound uses ultrasonic waves with non-ionization properties. The use of X-ray and ultrasound waves includes the medical and industrial fields. The research method uses literature studies by collecting and analyzing information from various credible sources obtained from 15 journals and 3 books. The results of the literature analysis include definitions, frequencies, and wavelengths, as well as the benefits and properties of X-rays and ultrasound. Although both are rarely used, some techniques combine them to increase image resolution and clarity.